Echocardiography is a feasible tool for assessing volume responsiveness - Lanspa, Michael J. (Journal of Thoracic Disease; Vol 9, No 5 (May 28, 2017): Journal of Thoracic Disease, 2017)
Shock remains a common and lethal syndrome. Despite several scientific advances, administration of intravenous crystalloid remains a key therapy. Inappropriate administration of fluid, however, results in increased mortality and morbidity. Over the past decade, it has become apparent that the conventional methods of assessing fluid responsiveness with static measures, like central venous pressure, are inaccurate. Several small studies have demonstrated the utility of echocardiographic measures that exploit heart-lung interactions to predict fluid responsiveness in selected patients. Vignon and colleagues recently compared multiple echocardiographic indices to predict fluid responsiveness in ventilated patients (1). Their study is commendable for its large size, and its inclusion of several different categories of acute circulatory failure, including sepsis, hypovolemia, and cardiogenic shock. Also commendable is their reporting of feasibility. The inferior vena cava, pulse pressure variation, and aortic velocity could not be measured in 22% of patients due to image acquisition or absence of sinus rhythm, while superior vena cava could be measured in nearly all patients. It also appeared that superior vena cava collapsibility was the most predictive of the echocardiographic measures.